The effects of the sound-image relationship within sound education for interactive media design - Yantac, Asim Evren; Ozcan, Oguzhan (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2006)
In the design of interactive systems, expression only through visuals is not adequate in all cases. This situation highlights the importance of sound design in interactive media design education and the view that the students getting this education should be directed towards interactivity aimed sound design. For this research, we examined projects and the related sound designs of the students taking the Sound Design course in the Interactive Media Design Program of Yildiz Technical University and studied the effects of the way the sound-image relationship has been handled. In respect to the findings of the research, the article reveals the criteria by which students can produce projects with more creative solutions regarding sound.
Keywords: creativity; design education; interactive media; sound and image; sound design; Art